Antibodies to human neutrophil antigen HNA‐3b implicated in cases of neonatal alloimmune neutropenia. Issue 5 (16th February 2018) - Lopes, Larissa Barbosa; Abbas, Samira Ali; Moritz, Elyse; Martins, Juliana Oliveira; Chiba, Akemi Kuroda; Langhi, Dante Mário; Bordin, José O.
Abstract : BACKGROUND: Neonatal alloimmune neutropenia results from maternal alloimmunization to human neutrophil antigens. The alloantibodies involved in neonatal alloimmune neutropenia are against human neutrophil antigens HNA‐1a, HNA‐1b, HNA‐1c, HNA‐1d, HNA‐2, HNA‐3a, HNA‐4a, HNA‐4b, and HNA‐5a; however, to date, antibodies specific to HNA‐3b have not been reported. STUDY DESIGN AND METHODS: Blood samples from 10, 000 unselected neonates were analyzed, resulting in the selection of 88 neutropenic newborns (neutrophil count <1.5 × 10 9 /L) from 83 mothers (three pairs of twins and one triplet). HNA‐3 genotyping was performed by polymerase chain reaction‐restriction fragment length polymorphism to identify the cases of maternal‐fetal HNA‐3 incompatibility. Serologic studies for detecting maternal HNA‐3 alloantibodies were performed with the granulocyte agglutination test, the white blood cell immunofluorescence test, and a LABScreen Multi‐HNA Kit. RESULTS: Genotyping studies identified 13 of 88 (14.8%) instances of maternal‐fetal HNA‐3 incompatibility, with all mothers typed as HNA‐3a/a and neonates typed as HNA‐3a/b. Serologic studies revealed that five of 13 (38.5%) mothers carried anti‐HNA‐3b plus human leukocyte antigen antibodies and that three of 13 (23.1%) mothers had anti‐HNA‐3b without human leukocyte antigen antibodies. CONCLUSION: Here, we report the first three cases of neonatal alloimmune neutropenia associated with HNA‐3b antibodies resulting in a neonatal alloimmune neutropenia incidence of one in 3333 live births.